Napoleon - Johnson, Paul; General Editor: Atlas, James (London Weidenfeld & Nicholson, 2002)
In this concise, astringent and wonderfully readable biography of Napoleon Bonaparte, Paul Johnson tells the story of his life and legacy, often surprising us with unexpected details and vivid insights.
Include Further Readings.
A short and vivid biography, which deconstructs the Napoleonic myth and reveals the grim reality of his rule.
Keywords: France -- Emperors -- Napoleon I, Emperor of the French, 1769-1821 -- Biography -- History -- Consulate and First Empire